Mentoring through small ensemble collaboration - Betts, Elizabeth (Kansas State University, 2020)
In this report, I describe a lesson in which 6th grade through 12th grade students fostered a mentor-mentee relationship while collaborating with each other, using technology, to perform simple duets. In this process, the older student created a recording as a practice tool for the younger student and provided feedback to them as they prepared their separate parts. The completed assignment included video recordings from both students, put together using the iMovie. As a result of close collaboration through technology, students developed a relationship across grade levels that they would not have been able to do otherwise. I have developed more as a teacher during the Kansas State Masters' of Music Program as I now actively look at finding efficiency and meaning in every aspect of my teaching. As the sole band director of my program, this has maximized the impact that I am able to have on my students. Another development in my teaching has been the more active role I have taken in culture building and relationships. Being rather new to my current position, this has proved to be helpful in recruiting and retention, as well as developing an atmosphere where students want to be. This has built a level of trust from both me and my students, allowing us to create and grow in an entirely new way.
Keywords: Small ensemble; Mentoring; Virtual